High Prevalence of Artemisinin-Resistant Plasmodium falciparum, Southeastern Sudan - Mariangela L’Episcopia; Albadawi A. Talha; Bakri Y.M. Nour; Ibrahim Mohamed Ahmed Sana; Emmanuelle Caspar; Lucas Thiebaut; Lucien Platon; Buze Chala; Laurence Ma; Lemu Golassa; Edvige Perrotti; Carlo Severini; et al. (Emerging Infectious Diseases)
We conducted a hospital-based cross-sectional study of Plasmodium falciparum in 2017 in southeastern Sudan. Among 257 P. falciparum samples, we found 22% harbored the pfkelch13 R622I mutation and 10.7% showed hrp2/3 gene deletions. Our findings highlight the urgent need for enhanced surveillance of drug- and diagnostic-resistant parasites in the Horn of Africa.